123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115 |
- from sympy.core.function import (Derivative, diff)
- from sympy.core.numbers import (Float, I, nan, oo, pi)
- from sympy.core.relational import Eq
- from sympy.core.symbol import (Symbol, symbols)
- from sympy.functions.elementary.piecewise import Piecewise
- from sympy.functions.special.delta_functions import (DiracDelta, Heaviside)
- from sympy.functions.special.singularity_functions import SingularityFunction
- from sympy.series.order import O
- from sympy.core.expr import unchanged
- from sympy.core.function import ArgumentIndexError
- from sympy.testing.pytest import raises
- x, y, a, n = symbols('x y a n')
- def test_fdiff():
- assert SingularityFunction(x, 4, 5).fdiff() == 5*SingularityFunction(x, 4, 4)
- assert SingularityFunction(x, 4, -1).fdiff() == SingularityFunction(x, 4, -2)
- assert SingularityFunction(x, 4, 0).fdiff() == SingularityFunction(x, 4, -1)
- assert SingularityFunction(y, 6, 2).diff(y) == 2*SingularityFunction(y, 6, 1)
- assert SingularityFunction(y, -4, -1).diff(y) == SingularityFunction(y, -4, -2)
- assert SingularityFunction(y, 4, 0).diff(y) == SingularityFunction(y, 4, -1)
- assert SingularityFunction(y, 4, 0).diff(y, 2) == SingularityFunction(y, 4, -2)
- n = Symbol('n', positive=True)
- assert SingularityFunction(x, a, n).fdiff() == n*SingularityFunction(x, a, n - 1)
- assert SingularityFunction(y, a, n).diff(y) == n*SingularityFunction(y, a, n - 1)
- expr_in = 4*SingularityFunction(x, a, n) + 3*SingularityFunction(x, a, -1) + -10*SingularityFunction(x, a, 0)
- expr_out = n*4*SingularityFunction(x, a, n - 1) + 3*SingularityFunction(x, a, -2) - 10*SingularityFunction(x, a, -1)
- assert diff(expr_in, x) == expr_out
- assert SingularityFunction(x, -10, 5).diff(evaluate=False) == (
- Derivative(SingularityFunction(x, -10, 5), x))
- raises(ArgumentIndexError, lambda: SingularityFunction(x, 4, 5).fdiff(2))
- def test_eval():
- assert SingularityFunction(x, a, n).func == SingularityFunction
- assert unchanged(SingularityFunction, x, 5, n)
- assert SingularityFunction(5, 3, 2) == 4
- assert SingularityFunction(3, 5, 1) == 0
- assert SingularityFunction(3, 3, 0) == 1
- assert SingularityFunction(4, 4, -1) is oo
- assert SingularityFunction(4, 2, -1) == 0
- assert SingularityFunction(4, 7, -1) == 0
- assert SingularityFunction(5, 6, -2) == 0
- assert SingularityFunction(4, 2, -2) == 0
- assert SingularityFunction(4, 4, -2) is oo
- assert (SingularityFunction(6.1, 4, 5)).evalf(5) == Float('40.841', '5')
- assert SingularityFunction(6.1, pi, 2) == (-pi + 6.1)**2
- assert SingularityFunction(x, a, nan) is nan
- assert SingularityFunction(x, nan, 1) is nan
- assert SingularityFunction(nan, a, n) is nan
- raises(ValueError, lambda: SingularityFunction(x, a, I))
- raises(ValueError, lambda: SingularityFunction(2*I, I, n))
- raises(ValueError, lambda: SingularityFunction(x, a, -3))
- def test_leading_term():
- l = Symbol('l', positive=True)
- assert SingularityFunction(x, 3, 2).as_leading_term(x) == 0
- assert SingularityFunction(x, -2, 1).as_leading_term(x) == 2
- assert SingularityFunction(x, 0, 0).as_leading_term(x) == 1
- assert SingularityFunction(x, 0, 0).as_leading_term(x, cdir=-1) == 0
- assert SingularityFunction(x, 0, -1).as_leading_term(x) == 0
- assert SingularityFunction(x, 0, -2).as_leading_term(x) == 0
- assert (SingularityFunction(x + l, 0, 1)/2\
- - SingularityFunction(x + l, l/2, 1)\
- + SingularityFunction(x + l, l, 1)/2).as_leading_term(x) == -x/2
- def test_series():
- l = Symbol('l', positive=True)
- assert SingularityFunction(x, -3, 2).series(x) == x**2 + 6*x + 9
- assert SingularityFunction(x, -2, 1).series(x) == x + 2
- assert SingularityFunction(x, 0, 0).series(x) == 1
- assert SingularityFunction(x, 0, 0).series(x, dir='-') == 0
- assert SingularityFunction(x, 0, -1).series(x) == 0
- assert SingularityFunction(x, 0, -2).series(x) == 0
- assert (SingularityFunction(x + l, 0, 1)/2\
- - SingularityFunction(x + l, l/2, 1)\
- + SingularityFunction(x + l, l, 1)/2).nseries(x) == -x/2 + O(x**6)
- def test_rewrite():
- assert SingularityFunction(x, 4, 5).rewrite(Piecewise) == (
- Piecewise(((x - 4)**5, x - 4 > 0), (0, True)))
- assert SingularityFunction(x, -10, 0).rewrite(Piecewise) == (
- Piecewise((1, x + 10 > 0), (0, True)))
- assert SingularityFunction(x, 2, -1).rewrite(Piecewise) == (
- Piecewise((oo, Eq(x - 2, 0)), (0, True)))
- assert SingularityFunction(x, 0, -2).rewrite(Piecewise) == (
- Piecewise((oo, Eq(x, 0)), (0, True)))
- n = Symbol('n', nonnegative=True)
- assert SingularityFunction(x, a, n).rewrite(Piecewise) == (
- Piecewise(((x - a)**n, x - a > 0), (0, True)))
- expr_in = SingularityFunction(x, 4, 5) + SingularityFunction(x, -3, -1) - SingularityFunction(x, 0, -2)
- expr_out = (x - 4)**5*Heaviside(x - 4) + DiracDelta(x + 3) - DiracDelta(x, 1)
- assert expr_in.rewrite(Heaviside) == expr_out
- assert expr_in.rewrite(DiracDelta) == expr_out
- assert expr_in.rewrite('HeavisideDiracDelta') == expr_out
- expr_in = SingularityFunction(x, a, n) + SingularityFunction(x, a, -1) - SingularityFunction(x, a, -2)
- expr_out = (x - a)**n*Heaviside(x - a) + DiracDelta(x - a) + DiracDelta(a - x, 1)
- assert expr_in.rewrite(Heaviside) == expr_out
- assert expr_in.rewrite(DiracDelta) == expr_out
- assert expr_in.rewrite('HeavisideDiracDelta') == expr_out
|